Asksia AI LOGO

Sia

Question
Math
Posted 9 months ago
For a given input value vv, the function hh outputs a value uu to satisfy the following equation.
2u+6v=9
-2 u+6 v=9


Write a formula for h(v)h(v) in terms of vv.
h(v)=
h(v)=

\square
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 1
Given the equation from asksia-ll calculation list: 2u+6v=9-2u + 6v = 9
step 2
To solve for uu in terms of vv, isolate uu on one side of the equation
step 3
Add 2u2u to both sides of the equation to get 6v=9+2u6v = 9 + 2u
step 4
Subtract 99 from both sides to get 6v9=2u6v - 9 = 2u
step 5
Divide both sides by 22 to solve for uu: u=3v92u = 3v - \frac{9}{2}
step 6
The function h(v)h(v) that outputs uu is therefore h(v)=3v92h(v) = 3v - \frac{9}{2}
Answer
h(v)=3v92h(v) = 3v - \frac{9}{2}
Key Concept
Solving a linear equation for a variable
Explanation
To find h(v)h(v), we isolate uu in the given equation and express it as a function of vv. The steps involve rearranging the equation and solving for uu.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question